All-Optical Basic Arithmetic Elements using Dark-Bright Solitons Conversion Control - Somsak Mitatha; Khanthanou Luangxaysana; Preecha Yupapin (My University, 2014)
In this paper, we propose a new design for all-optical basic arithmetic elements using optical technique namely dark-bright solitons conversion control within an optical add-drop filter. In operation, all-optical data input logic ‘0’, ‘1’ is formed by dark soliton (D) and bright soliton (B) pulses, respectively. The conversion behaviour between dark and bright soliton pulses can be obtained and formed the logic pulses by a π/2 phase shifted device such as an optical coupler, in which the binary logic operation can be formed simultaneously at the thought and drop ports, respectively. In all-optical NAND gate and S-R flip-flop application can be recognized as a simple and flexible system for forming the logic switching system. Numerical simulation results are obtained and confirmed for the useful application, in which the advanced logical system can be operated.
Keywords: Optical burst switching; Optical Network Technologies